Analisis Efisiensi Penggunaan Input Produksi pada Usahatani Bawang Merah di Desa Songan B, Kecamatan Kintamani,Kabupaten Bangli - WIDIAWATI WIDIAWATI; I DEWA GEDE RAKA SARJANA; A.A.A WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Efficiency Analysis of the Use of Production Input on Shallot Farming in Songan B Village, Kintamani Sub-District, of Bangli Regency Bali is a tourism area and a potential market for shallot business. One of the shallotproduction centers in Bali is Songan B Village, Kintamani Sub-District, BangliRegency. Fluctuating shallot production is thought to be due to the inefficient use ofproduction inputs so that it is needed to analyze the efficiency of the use of productioninputs. This study aims to determine the effect and efficiency of the use of shallotproduction inputs. The study was conducted in Songan B Village by analyzingproduction inputs such as area of arable land, seeds, manure, NPK fertilizer, solidpesticides, liquid pesticides and labor by using the Cobb-Douglas productionfunction.The data used were data in the March, April, and May planting season of 48respondents determined by a simple random method. Efficiency can be seen from thecomparison of marginal production values and production input prices. The resultsshowed that the area of cultivated land, NPK fertilizer and labor had a positive effect onthe shallot production. Solid pesticides negatively affected the shallot production, whilethe seeds, manure and liquid pesticides had no significant effect. The inefficient use ofproduction inputs is the area of cultivated land and NPK fertilizer, so that its use must be increased, while other production inputs are inefficient that their uses must bereduced.